Effectiveness and safety of biosilicate-enhanced bleaching gels on enamel with early erosion lesion - Dascanio, Rafael; de Oliveira Ribeiro, Rafael Antonio [UNESP]; Coelho, Camila Siqueira Silva; Souza, Marina Trevelin; Kury, Matheus; Zanotto, Edgar Dutra; de Souza Costa, Carlos Alberto [UNESP]; Cavalli, Vanessa (Wiley, 2024)
Aim: This study evaluated the efficacy and cytotoxicity of 35% hydrogen peroxide (HP) gel incorporated with 10% (w/w) biosilicate (BioS) on sound enamel and early-stage enamel erosion lesions. Methods: Discs of enamel/dentin were selected, subjected to erosive cycles (0.3% citric acid, pH 2.6), and treated with (n = 8): HP (35% HP, positive control); HP_BioS [carboxymethyl cellulose (CMC) + HP + BioS]; BioS (CMC + BioS); CMC (negative control). The discs were adapted to artificial pulp chambers with the enamel exposed for bleaching, and the dentin facing toward the culture medium (Dulbecco's modified Eagle's medium [DMEM]). Bleaching was performed in three 30-min sessions at 7-day intervals. After bleaching, the diffusion product (DMEM extract + diffused HP) was pipetted onto MDPC-23 odontoblastic cell line and inoculated. Color parameters (ΔL, Δa, Δb), color change (ΔE00), and changes in whiteness index (ΔWID) were determined before (T0) and after the last bleaching session (T3). Cell viability (MTT, %), H2O2 diffusion (μg/mL), oxidative cell stress (OxS), and cell fluorescence (live/dead assay, in confocal microscopy) were assessed (ANOVA/Tukey; α = 0.05). Results: No difference in ΔL, Δa, Δb, ΔE00, and ΔWID were found between HP and HP_BioS (p > 0.05). The incorporation of BioS decreased the HP diffusion into the substrates and mitigated oxidative stress in early-stage eroded enamel (p < 0.05). HP_BioS presented significantly higher cell viability compared with HP under erosion conditions. Live/dead assay indicated that BioS_HP maintained viability with larger clusters of viable cells. Conclusion: Incorporating BioS into HP maintained bleaching effectiveness, favored cell viability, reduced the oxidative stress, and the cytotoxicity in teeth with early-stage erosion. Clinical Significance: BioS formulation showed promising results for reducing cytotoxicity in patients seeking tooth bleaching and presenting undetectable early-stage erosion.
Keywords: biosilicate; cytotoxicity; tooth bleaching